Pulmonary embolism concurrent with lung cancer and central emboli predict mortality in patients with lung cancer and pulmonary embolism - Cha, Seung-Ick; Shin, Kyung-Min; Lim, Jae-Kwang; Yoo, Seung-Soo; Lee, Shin-Yup; Lee, Jaehee; Kim, Chang-Ho; Park, Jae-Yong; Lee, Won-Kee; Jung, Chi-Young (Journal of Thoracic Disease, 2017)
Background: Patients with lung cancer commonly experience pulmonary embolism (PE). The aim of the present study was to examine the clinical features of patients with lung cancer and PE and to investigate prognostic factors in these patients. Methods: This retrospective study divided patients with lung cancer and PE into a group of patients with PE diagnosed concomitantly with lung cancer (concurrent group) and a group with PE detected after lung cancer (sequential group), compared the clinical characteristics of patients in the two groups, and investigated prognostic factors in these patients. Results: The study population consisted of the concurrent group [27 patients (10.1%)] and the sequential group [240 patients (89.9%)]. The concurrent group exhibited higher percentages of stage I cancer at the diagnosis of PE [6 (22.2%) vs. 8 (3.3%), P